INVESTIGATING MATHEMATICAL LOGICS IN SURAH YUSUF VERSE 25 UNTIL 29 - Nisfulaila, Intan; Mukmin, Muhammad Islahul; Sasongko, Dimas Femy (Proceeding of International Conference on Islamic Education (ICIED); Vol 3 No 1 (2018): Proceeding of International Conference on Islamic Education (ICIED), 2018)
Al Qur’an is Muslims’ holy book which is not only as the source of laws but also as the source of knowledge. One of the knowledge that is contained in Al Qur’an and interesting to discuss is Mathematical Logics in Surah Yusuf verse 25 until 29. These verses contain not only exemplary stories for Muslims but also contain Mathematical Logics which worth to be understood by mankind — mathematical Logics in this verse such as implication and drawing a conclusion based on Ponens Modus.